2009
DOI: 10.1051/0004-6361/200912142
|View full text |Cite
|
Sign up to set email alerts
|

Deep census of variable stars in a VLT/VIMOS field in Carina

Abstract: Aims. We searched for variable stars in deep V-band images of a field towards the Galactic plane in Carina. Methods. The images were taken with the VIMOS instrument at ESO VLT during 4 contiguous nights in April 2005. We detected 348 variables among 50 897 stars in the magnitude range between V = 15.4 and V = 24.5 mag. After detection, we classified the variables by a direct eye inspection of their light curves. Results. All variable objects besides 9 OGLE transits in the field are new discoveries. We provide … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…The simple search method we applied to our short-period data, the eye inspection of all light curves, turned out to be very effective. It is interesting that we have obtained almost the same rate of eclipsing/ellipsoidal systems as in our previous search in a VIMOS field in Carina (Pietrukowicz et al 2009). The binary detection rate would be very probably higher if the observations lasted considerably longer than only two days.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The simple search method we applied to our short-period data, the eye inspection of all light curves, turned out to be very effective. It is interesting that we have obtained almost the same rate of eclipsing/ellipsoidal systems as in our previous search in a VIMOS field in Carina (Pietrukowicz et al 2009). The binary detection rate would be very probably higher if the observations lasted considerably longer than only two days.…”
Section: Discussionsupporting
confidence: 81%
“…We used the DOPHOT package (Schechter et al 1993) Fernández et al (2006), Díaz et al (2007), Hoyer et al (2007), Minniti et al (2007), Pietrukowicz et al (2009) and Pietrukowicz et al (2010).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All effects that influence the JHK lightcurve are likely also visible in the mid-IR. Our fraction of variable objects with a class III SED is similar (1.8%) to what Wolk et al found. In the optical and near-IR, the fraction of variable field stars is lower than that value (Pietrukowicz et al 2009(Pietrukowicz et al , 2012Wolk et al 2013b).…”
Section: Evolutionary Trends Of the Variabilitymentioning
confidence: 99%
“…At faint limits the colors of reddened background stars can mimic faint cluster members. This issue can be combated with multiple observations to identify members by variability, since only a tiny fraction of field stars are variable (e.g., Morales-Calderón et al 2009;Pietrukiwicz et al 2009;Wolk et al 2013aWolk et al , 2013b.…”
Section: Introductionmentioning
confidence: 99%